LEARNING IN MATHEMATICS: EVOLUTION OF METHODOLOGIES AND ASSESSMENT IN BASIC EDUCATION - Cazuza da Silva Neto, Raimundo; Bruno Braga Bezerra, Alex (Journal of Interdisciplinary Debates, 2023)
The present study on learning in mathematics: evolution of methodologies and assessment in basic education guides a problem that has evolved, which is the issue of learning, assessment and school planning that guides the teacher as an agent of facilitating education. Therefore, it is challenged to rethink the decision-making resulting from this planning and its mathematical evaluation practice. To corroborate the theme, the applied methodology is action research. It is noteworthy that constructivism preaches that mathematics education has been a new paradigm in stimulating mathematical learning and the development of reasoning, even great thinkers such as PIAGET and VYGOTSKY cite their contributions to learning, problem situations, understanding of operations and applications.